Biological activity of human IgE monoclonal antibodies targeting Der p 2, Fel d 1, Ara h 2 in basophil mediator release assays - Pena-Castellanos, Glorismer; Smith, Bryan R. E.; Pomés, Anna; Smith, Scott A.; Stigler, Maria A.; Widauer, Hannah L.; Versteeg, Serge A.; van Ree, Ronald; Chapman, Martin D.; Aglas, Lorenz (Frontiers in Immunology, 2023)
Background: Human Immunoglobulin E monoclonal antibodies (hIgE_mAb) are unique tools for investigating IgE responses. Here, the biological activity of hIgE_mAb, derived from immortalized B cells harvested from the blood of allergic donors, targeting three allergens (Der p 2, Fel d 1 and Ara h 2) was investigated. Methods: Three Der p 2-, three Fel d 1- and five Ara h 2-specific hIgE_mAb produced by human B cell hybridomas, were combined in pairs and used to passively sensitize humanized rat basophilic leukemia cells and compared with sensitization using serum pools. Sensitized cells were stimulated with corresponding allergens (recombinant or purified), allergen extracts or structural homologs, having 40-88% sequence similarity, and compared for mediator (β-hexosaminidase) release. Results: One, two and eight pairs of Der p 2-, Fel d 1- and Ara h 2-specific hIgE_mAb, respectively, produced significant mediator release (>50%). A minimum hIgE_mAb concentration of 15-30 kU/L and a minimum antigen concentration between 0.01-0.1 µg/mL were sufficient to induce a pronounced mediator release. Individual sensitization with one Ara h 2-specific hIgE_mAb was able to induce crosslinking independently of a second specific hIgE_mAb. Der p 2- and Ara h 2-specific mAb showed a high allergen specificity when compared to homologs. Mediator release from cells sensitized with hIgE_mAb was comparable to serum sensitization. Conclusion: The biological activity of hIgE_mAb reported here provides the foundation for novel methods of standardization and quality control of allergen products and for mechanistic studies of IgE-mediated allergic diseases, using hIgE_mAb.